A Fluidisation Mechanism for Secondary Hydroeruptions in Pyroclastic Flow Deposits - Gilbertson, M. A.; Taylor, A.; Mitchell, S. J.; Rust, A. C. (Frontiers in Earth Science, 2020)
Heating of water under hot pyroclastic flow deposits can drive hydroeruptions, forming craters and aprons of secondary deposits. According to the established conceptual model, steam pressure builds until failure of the pyroclastic overburden, and a relatively low permeability (fine-grained) cap promotes secondary explosions. We explore a complementary model where the stress from drag related to gas flow up through the particle interstices, is comparable in magnitude to the static pressure difference between the base and the top of the pyroclastic flow deposit. The drag force supports (part of) the weight of the particles and so reduces inter-particle friction; in a mono-sized bed this friction is effectively eliminated at the ‘minimum fluidisation velocity’, which depends on the size and density of the particles. Through analogue experiments we show that violent outbursts can be generated when there are vertical variations in the minimum fluidisation velocities of granular materials. We ran experiments with layers of particles with different sizes or size distributions (bi-modal with different proportions of fine and coarse particles) in a tank with a porous base allowing a distributed upward airflow through them. A finer-grained layer capping a coarser layer does not generate jets of particles or craters; rather, increased gas flux leads to fluidisation of first the fine, and then the coarse (lower), layer. However, when the upper layer is coarser, for some combinations of layer thicknesses and grain sizes, the bed domes upward as a gas pocket grows within the finer layer; when the gas pocket penetrates the top of the bed, it forms a crater and erupts particles. The gas velocity when doming initiates is greater than that calculated for the weight of the top layer to be balanced by drag and the pressure difference across that layer. This discrepancy is explained by the layers having a strength (from inter-particle friction), consistent with the observed dependence of the initiation velocity on the absolute thickness of the layer. Using data from Mt St Helens 1980 deposits, we show that the drag-related trigger observed in the laboratory is a feasible mechanism for secondary hydroeruptions through pyroclastic flow deposits.